Effects of Fintech Firms on Banking Profitability in ASEAN-5 during the Pandemic COVID-19 - Pham, Tien Phat; Nguyen, Diep T. N.; Hoang, Sinh Duc; Tran, Tri Ba (Asian Academy of Management Journal of Accounting and Finance, 2025)
Fintech and fintech businesses have advanced banking and finance innovation. Since COVID-19 in 2020, fintech has accelerated the adoption of digital technology in banks to help individual and business customers during the crisis and the new normal. This research seeks to assess the correlations among fintech firms (FIN) and bank performance metrics, specifically Return on Total Assets (ROA) and Return on Equity (ROE), alongside bank attributes, i.e., Total Assets (SIZE), Leverage (LEV), Loans (LOAN), Deposits (DEPO) and Scale (SCA). Additionally, it investigates the influence of FIN on these essential bank profitability indicators in conjunction with macroeconomic variables, including GDP, Consumer Price Index (INF) and the occurrence of COVID-19. Based on consumer and disruptive innovation theories, dataset including 57 banks from Indonesia, Thailand, Malaysia, the Philippines and Vietnam from 2017 to 2021, the study used the dynamic panel model with the two-step Generalised Method of Moments (GMM) estimator, to demonstrate that fintech firms negatively affected bank profitability across ASEAN countries. Fintech hurts small banks more than large banks, and COVID-19 exacerbated its negative impact on ASEAN-5 bank profitability.